The influence of fine aggregate on the bituminous mixture mechanical behaviour - Pais, Jorge C. (2003)
The mechanical behaviour of a bituminous mixture is influenced by its composition. One of the compositional parameters that can change the bituminous performance in a pavement is the gradation of the fine aggregates. This paper presents the stiffness, fatigue and permanent deformation results of bituminous mixtures used in wearing and base courses. For each type of mixture, five mixtures were defined, by changing the gradation curve (from more to less fine aggregates). All mixtures were produced and compacted in laboratory. Specimens for tests were obtained by cored and sawed from compacted slabs. For stiffness and fatigue, tests were executed on four point bending beam on controlled strain, whereas for permanent deformation tests were the repetitive simple shear test at constant height.